Geology and Wine 5. Provenance of Okanagan Valley Wines, British Columbia, Using Trace Elements: Promise and Limitations - Taylor, Viven; Longerich, Henry; Greenough, John (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2002)
Summary The trace element compositions of 52 Okanagan wines from 26 vineyards were examined to test for correlations between wine and soil/bedrock composition, and to estimate total variability in Okanagan wine composition. Trace element concentrations in wines analysed are shown to provide verification of vineyard of origin, indicating that trace element compositions are influenced by vineyard geology, although geologic and environmental/climatic influences could not be clearly differentiated from possible wine processing influences in this reconnaissance study. Cluster analysis of Okanagan white wines using Al, Mn, V, Sr, Rb, Mo, Sb,Co, Zn, and U groups wines from the same vineyard, as well as showing a general north-south trend in wine chemistry related to vineyard location within the valley.